Parental Involvement in the Educational Process as a Potential Factor in Tachers’ Experience of Work Stress - Tekavc, Janja; Vončina, Teja (Revija za elementarno izobraževanje, 2023)
For teachers, working with parents can represent an important source of work stress. The study involved 248 Slovenian primary school teachers, who completed a questionnaire consisting of scales on perceived stress and job satisfaction and a questionnaire on cooperation with parents. The results showed that teachers are satisfied with their job, although they do associate it with high levels of stress. Among the different forms of engagement with parents, the most stressful was the presence of parents during the educational process and parent-teacher association meetings. Teachers also perceive high levels of stress when parents interfere in and control their work.
Keywords: teachers, parents, stress, job satisfaction, social-emotional competences, relational competence